2018
DOI: 10.3389/fphar.2018.00053
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Lipidomics and Phenotype Study Reveals Protective Effect and Biochemical Mechanism of Traditionally Used Alisma orientale Juzepzuk in Chronic Kidney Disease

Abstract: Alisma orientale Juzepzuk (AO) is widely used for various diuretic and nephropathic treatments in traditional Chinese medicines (TCM). In a clinical setting, AO is used as both a lipid-lowering and tubular interstitial fibrosis agent. However, the mechanisms of AO for the treatment of renal interstitial fibrosis and abnormal lipid metabolism are not well-understood. In this study, pharmacological and UPLC-HDMS-based lipidomic approaches were employed to investigate the lipid-lowering and tubular interstitial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 63 publications
1
38
0
2
Order By: Relevance
“…Metabolomics technique has been extensively applied to the study of TCM and natural products . In agreement with the holistic thinking of TCM, metabonomics has shown potential to reveal the biological foundation and mechanism of TCM …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Metabolomics technique has been extensively applied to the study of TCM and natural products . In agreement with the holistic thinking of TCM, metabonomics has shown potential to reveal the biological foundation and mechanism of TCM …”
Section: Discussionmentioning
confidence: 94%
“…[37 -40] In agreement with the holistic thinking of TCM, metabonomics has shown potential to reveal the biological foundation and mechanism of TCM. [41][42][43][44][45][46][47] The crocin family is the particular ingredients that occur naturally in stigmas of saffron when compared with other parts. According to the pathway of crocin Figure 5), crocetin can be converted into glucosyl crocetin and finally transferred into crocin.…”
Section: Discussionmentioning
confidence: 99%
“…Alismatis rhizome (AR), as a well-known herb, exhibited lipid-lowing and renoprotective effects [104][105][106][107]. Our results indicated that AR treatment retarded renal fibrosis by downregulating inflammation and TGF-β1/Smad pathway in CKD rats [108]. Our further study demonstrated that alisol B 23-acetate treatment significantly amileriated podocytes and tubular epithelial cells by inhibiting activation of Wnt/βcatenin, oxidative stress and inflammation [109].…”
Section: Targeting Tgf-β1/smad Signaling By Isolated Compoundsmentioning
confidence: 85%
“…Alismatis rhizome (AR), the dried rhizome of Alisma orientale (Sam.) Juzep, exhibited diuretic, antihyperlipidemic, and renoprotective effects that were also confirmed by our previous studies . Our recent study demonstrated that triterpenoid was the main component of AR, and further study showed that the novel tetracyclic triterpenoid 25‐O‐methylalisol F inhibited EMT by suppressing the Wnt/β‐catenin signaling pathway as well as the phosphorylation of Smad3 signaling in both NRK‐52E and NRK‐49F cells (Figure and Table ).…”
Section: Small Molecules Against Emtmentioning
confidence: 99%